Penataan ruang perpustakaan untuk meningkatkan minat baca siswa di Perpustakaan Ibnu Sina SMP Negeri 12 Pontianak - Sahidi, Sahidi; Sulastri, Umi; Hanum, Atiqa Nur Latifa (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research aims to determine the spatial planning of libraries in increasing students' interest in reading as well as the spatial planning strategies used to attract students' interest in reading. The method used is a qualitative method, by obtaining data and then analyzing it using descriptive analysis. Data collection techniques through observation, interviews and documentation techniques. Interviews were conducted with 4 informants. Data analysis techniques use data reduction, data presentation and conclusions. Data validity techniques use four techniques: credibility, transferability, dependability, confirmability. The results of the research show that the spatial planning of the Ibnu Sina library at SMP Negeri 12 Pontianak as a whole has been running but has not yet reached the ideal standard based on the 2015 school library spatial planning guidelines. Indicators that are still lacking are the aspects of airing, instructions or signs. Meanwhile, the indicators for coloring, security, safety and accessibility have been met. The strategy used to increase interest in reading in the library is through physical and non-physical arrangements in the form of library facilities in the form of collection development, literacy activities and promotions which are considered to have been implemented although not yet optimal and still need to be improved.